Improving the Assessment of Resident Competency: Physical Medicine and Rehabilitation Milestones 2.0. (February 2021) - Taylor, Charles M.; Baer, Heather; Edgar, Laura; Jenkins, Jeffrey G.; Harada, Nancy; Helkowski, Wendy M.; Zumsteg, Jennifer M.; Francisco, Gerard E.; Sabharwal, Sunil; Hamilton, Rita G.; Mallow, Michael
Abstract : Abstract: In 2015, the Accreditation Council for Graduate Medical Education published the Physical Medicine and Rehabilitation Milestones 1.0 as part of the Next Accreditation System. This was the culmination of more than 20 yrs of work on the part of the Accreditation Council for Graduate Medical Education to improve graduate medical education competency assessments. The six core competencies were patient care, medical knowledge, systems-based practice, practice-based learning and improvement, professionalism, and interpersonal and communication skills. While providing a good foundation for resident assessment, the Physical Medicine and Rehabilitation Milestones 1.0 was not without faults. With input from program directors, national organizations, and the public, the Physical Medicine and Rehabilitation Milestones 2.0 strives to further advance resident assessment, providing improvements through the integration of the harmonized Milestones and the addition of a supplemental guide.